Writing the Goodlife : Mexican American Literature and the Environment - Ybarra, Priscilla Solis (Book collections on Project MUSE., 2016)
"The book looks to long-established traditions of environmentalist thought alive in Mexican American literary history over the last 150 years"--Provided by publisher.